Mid- and long-term mortality risk factors after COVID-19 hospitalization: A retrospective observational study in Peru - Max Carlos Ramírez-Soto; Hugo Arroyo-Hernández (Vaccine: X)
Background: Recent studies have demonstrated the long-term mortality risk in COVID-19 survivors. However, the risk factors for mid- and long-term mortality after COVID-19 hospitalization in the Peruvian population are unknown. We evaluated risk factors associated with mid- and long-term mortality after COVID-19 hospitalization. Methods: We conducted a retrospective observational study in survivors of SARS-CoV-2 infection discharged from hospital during 2020–2023, using open data from the Ministerio de Salud, Peru. The main outcome measures were mortality among all survivors of SARS-CoV-2 infection at mid-term (61 to 364 days after hospital discharge) and long-term (≥1 year after hospital discharge). Results: Of the 97,249 COVID-19 survivors who were discharged from hospital, 523 patients died within 61 to 364 days of discharge and 219 patients died after 1 year or more since they were discharged. The older age (adjusted ratio hazards [aHR], 3.46; 95 % CI, 2.87–4.17; p < 0.001 to mid-term; and aHR, 3.48; 95 % CI, 2.63–4.61; p < 0.001 to long-term), oxygen support (aHR, 1.64; 95 % CI, 1.30–2.07; p < 0.001 to mid-term), and the hospitalization stay of 4 to 9 days (aHR, 1.54; 95 % CI, 1.18–2.00; p = 0.001 to mid-term; and aHR, 1.64; 95 % CI, 1.04–2.58; p = 0.034 to long-term) and ≥ 10 days (aHR, 2.44; 95 % CI, 1.89–3.17; p < 0.001 to mid-term; and aHR, 2.98; 95 % CI, 1.89–4.68; p < 0.001 to long-term) were associated with increased mortality risk. Compared with the unvaccinated, administration of 1 to 2 or 3 to 4 doses of the SARS-CoV-2 vaccine before or after hospitalization was associated with a reduced risk of death in the mid- and/or long-term. Conclusion: Although older age and longer hospital stay were associated with an increased risk of death after COVID-19 hospitalization in the mid- and long-term, and oxygen support increased the risk of death in the mid-term, vaccination against SARS-CoV-2 reduced the risk of death.